2021
DOI: 10.1371/journal.pone.0255800
|View full text |Cite
|
Sign up to set email alerts
|

Should we keep some distance from distancing? Regulatory and post-regulatory effects of emotion downregulation

Abstract: Emotion regulation is an indispensable part of mental health and adaptive behavior. Research into emotion regulation processes has largely focused on the concurrent effects of volitional emotion regulation. However, there is scarce evidence considering post-regulatory effects with regard to neural mechanisms and emotional experiences. Therefore, we compared concurrent effects of cognitive emotion regulation with effects at different (immediate, short- and long-term) time intervals. In an fMRI study with N = 46… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
5
1
Order By: Relevance
“…stronger activation of amygdala and ventromedial prefrontal cortex, reduced negative feelings), but not for distancing. In contrast, in previous studies that included emotional down-regulation, but not up-regulation, we and others (Diers et al, 2021;Walter et al, 2009) observed a partial reversal of regulation effects immediately after the stimulation phase as well as during immediate and prolonged re-exposure experiments.…”
Section: Temporal Dynamics Of Up-and Down-regulationcontrasting
confidence: 99%
See 3 more Smart Citations
“…stronger activation of amygdala and ventromedial prefrontal cortex, reduced negative feelings), but not for distancing. In contrast, in previous studies that included emotional down-regulation, but not up-regulation, we and others (Diers et al, 2021;Walter et al, 2009) observed a partial reversal of regulation effects immediately after the stimulation phase as well as during immediate and prolonged re-exposure experiments.…”
Section: Temporal Dynamics Of Up-and Down-regulationcontrasting
confidence: 99%
“…by assuming a personal or physical distance. The "distance" and "permit" strategies are identical to those in our previous work (Diers et al, 2021).…”
Section: Emotion Regulation Task (Timepoints 1 and 2)mentioning
confidence: 70%
See 2 more Smart Citations
“…The paradigm was based on previous designs to study emotion regulation (Diers et al, 2021; Gärtner et al, 2019; Kanske et al, 2011; McRae et al, 2012). A schematic illustration can be found in Figure 2.…”
Section: Methodsmentioning
confidence: 99%